2018
DOI: 10.1002/jmri.26034
|View full text |Cite
|
Sign up to set email alerts
|

Improving lymph node characterization in staging malignant lymphoma using first‐order ADC texture analysis from whole‐body diffusion‐weighted MRI

Abstract: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;48:897-906.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 43 publications
0
5
0
2
Order By: Relevance
“…Among the potential perspectives of the use of whole-body MRI to image patients with lymphoma, new and interesting fields of application include the computer assisted diagnosis, the texture analysis and the radiomics [55][56][57][58][59]. Several authors proposed the use of CAD to improve the lesion (damage) segmentation and the ADC value calculation in other tumors [55].…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the potential perspectives of the use of whole-body MRI to image patients with lymphoma, new and interesting fields of application include the computer assisted diagnosis, the texture analysis and the radiomics [55][56][57][58][59]. Several authors proposed the use of CAD to improve the lesion (damage) segmentation and the ADC value calculation in other tumors [55].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Texture analysis can be used to assess the spatial pattern and arrangement of pixel intensities in images to detect thetumoral heterogeneity, which several authors have shown, to have non-negligible correlations with tumor behavior, prognosis and response to treatment. In this setting, a relatively recent work by De Paepe et al has shown that the first order texture analysis of the ADC values improves the diagnostic performance of DWI in the characterization of locations of lymphoma if compared to the simple ADC average value calculation [58]. Similarly, a recent interesting paper on the texture analysis of post contrast T1 weighted images reported the high diagnostic performance in differentiating follicular from DLBCL that can be a valuable tool to identify the aggressive transformation of i-NHL [59].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In this study, we did not analyze or compare quantitative ADC values related to DWI because there are currently no validated single cut-off values to differentiate positive from negative lymph nodes, although lower values have been positively correlated with malignancy, whereas higher values indicate normal histology [25,30]. Future comparative studies between SUV max and ADC values could clarify the correlation (that we expect to be negative or inverse) between the quantitative data offered by these two imaging modalities in the characterization of malignant lymph nodes [31].…”
Section: Discussionmentioning
confidence: 99%
“…K. de Paepe с соавт. [13] обследовали пациентов с НХЛ и пришли к аналогичному выводу -ИКД пораженных ЛУ средостения и брюшной полости выше, чем ИКД ЛУ других анатомических областей, что авторы объясняют эффектом частичного объема и двигательными артефактами, связанными с дыханием и перистальтикой кишечника. D. Albano с соавт.…”
unclassified
“…Некоторые авторы указывают на отсутствие отличий между значениями ИКД при ЛХ и НХЛ[9], агрессивных и индолентных НХЛ[7], другими авторами получены противоположные результаты[12]. Эти расхождения могут быть связаны с влиянием на значения ИКД ряда клинических и технических факторов, что изучено недостаточно[13][14][15].Во многих работах исследована диагностическая эффективность МРТ-ДВИ всего тела по сравнению с позитронной эмиссионной томографией, комбинированной с компьютерной томографией (ПЭТ/КТ)[3, 6,14]. При интерпретации ПЭТ/КТ для дифференциации нормальных тканей и опухолевых очагов используют количественный показатель уровня метаболизма глюкозы -стандартизованный показатель накопления.…”
unclassified